2019
DOI: 10.1016/j.ejca.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between immune subtypes and consensus molecular subtypes in colorectal cancer identifies novel tumour microenvironment profiles, with prognostic and therapeutic implications

Abstract: Background: Solid tumour growth is the consequence of a complex interplay between cancer cells and their microenvironment. Recently, a new global transcriptomic immune classification of solid tumours has identified six immune subtypes (ISs) (C1eC6). Our aim was to specifically characterise ISs in colorectal cancer (CRC) and assess their interplay with the consensus molecular subtypes (CMSs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 25 publications
3
52
1
Order By: Relevance
“…While NK cells were highly enriched in CMS1 tumours, increased fractions were also found in CMS3 tumours. Soldevilla et al also suggested that an inflammatory immune subtype was present in CMS3 as well as CMS4 tumours [35]. In line with previous findings, macrophages were found to be slightly enriched in CMS1 tumours and were mainly of HLA-DR + M1 type in this CMS subgroup.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…While NK cells were highly enriched in CMS1 tumours, increased fractions were also found in CMS3 tumours. Soldevilla et al also suggested that an inflammatory immune subtype was present in CMS3 as well as CMS4 tumours [35]. In line with previous findings, macrophages were found to be slightly enriched in CMS1 tumours and were mainly of HLA-DR + M1 type in this CMS subgroup.…”
Section: Discussionsupporting
confidence: 72%
“…The more comprehensive studies of immune infiltration in CRC have used transcriptomics to evaluate the immune response in different molecular subgroups of CRC, including the gold standard CMS subgroups [18,[33][34][35][36]. In brief, the four CRC CMS groups are shown to display relevant differences when it comes to immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Soldevilla et al [ 63 ] evaluated the distribution of six immune subtypes proposed by Thorsson et al [ 64 ] among each CMS subtype in TCGA samples. In a total of 625 samples, the C1 wound healing subtype (77%) was the most predominant, followed by the C2 INF-γ dominant subtype (17%).…”
Section: Biomarkers Associated With Immune Microenvironment and Immunmentioning
confidence: 99%
“…CRC is the result of accumulated genetic, epigenetic, and endocrine aberrations [11,22]. The limitations of previous studies are that they focused on a single cohort study or results from a single database [23][24][25]. In the present study, we analyzed two microarray datasets GEO40967 and GEO8671 from GEO and RNA sequencing data form TCGA.…”
Section: Discussionmentioning
confidence: 99%